Gamelan Gambang: Educational Implications within a Community-Based Arts Education Framework - Lanus, I Ketut; Hartono; Raharjo, Eko (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2026)
This article examines Gamelan Gambang as a medium for the development of community-based arts education, with a particular focus on the preservation of Bali’s local cultural values. Gamelan Gambang is a sacred gamelan ensemble traditionally performed in Balinese religious ceremonies, especially within the context of mortuary rites. Beyond its musical and ritual functions, the ensemble embodies philosophical, spiritual, and social values that are highly relevant for transformation into contextualized arts education practices. Through a community-based arts education approach, Gamelan Gambang may serve not only as an instrument for aesthetic learning but also as a vehicle for strengthening cultural identity and transmitting local wisdom. This article elaborates the theoretical framework of community-based arts education, outlines strategies for implementing tradition-oriented learning, and discusses both the challenges and opportunities involved in revitalizing Gamelan Gambang as an educational medium. The study recommends an integrative collaboration between formal educational institutions and local communities in developing participatory arts learning models that are rooted in local values while remaining adaptive to contemporary social transformations.